1, 2, 3, 4-Tetrahydroisoquinoline (THIQ) as privileged scaffold for anticancer de novo drug design. (3rd October 2021) - Faheem,; Karan Kumar, Banoth; Venkata Gowri Chandra Sekhar, Kondapalli; Chander, Subhash; Kunjiappan, Selvaraj; Murugesan, Sankaranarayanan
ABSTRACT: Introduction : Cancer is a dreadful disorder that is emerging as one of the leading causes of mortality across the globe. The complex tumor environment, supplemented with drawbacks of the existing drugs, has made it a global health concern. The Tetrahydroisoquinoline (THIQ) ring holds an important position in medicinal chemistry due to its wide range of pharmacological properties. Several THIQ based natural products have been previously explored for their antitumor properties, making it a vital scaffold for anticancer drug design. Areas covered : This review article addresses the potential of THIQ as anticancer agents. Various medicinal chemistry strategies employed for the design and development of THIQ analogs as inhibitors or modulators of relevant anticancer targets have been discussed in detail. Moreover, the common strategies employed for the synthesis of the core scaffold are also highlighted. Expert opinion : Evidently, THIQs have tremendous potential in anticancer drug design. Some of these analogs exhibited potent activity against various cancer molecular targets. However, there are some drawbacks, such as selectivity that need addressing. The synthetic ease for constructing the core scaffold complimented with its reactivity makes it ideal for further structure-activity relationship studies. For these reasons, THIQ is a privileged scaffold for the design and development of novel anticancer agents.